Fink's integrated course design and taxonomy: The impact of their use in a “Basics of Dental Anatomy” course (2021)
This study aimed to assess whether the adjustment of Fink's Model of Integrated Course Design (ICD) with his Taxonomy of Significant Learning (hereinafter referred to as “ICD/SL”) affected the academic performance of students at Universidad El Bosque in the “Basics of Dental Anatomy” course. For this purpose, 3 academic groups were selected: 2018/1 (55 students), 2018/2 (79 students), and 2019/1 (57 students). The control group, 2018/1, was taught without ICD/SL; the 2 treatment groups, 2018/2 and 2019/1, was taught with ICD/SL, which applied revised learning goals based on Fink's Taxonomy and new teaching and evaluation activities. The assessment of academic performance was based on a Likert scale to position student results in each grade score report. Statistical analysis was performed through the Kruskal‐Wallis test and P‐value through the Mann‐Whitney U test and Fisher exact test. The results indicated that the treatment groups evidenced better academic performance in the summative assessment of the partial and final grades. In the treatment groups, 64% to 97% of students were in the High to Excellent segment; in comparison, this percentage in the control group was 44% to 65%. The course's rate of failure dropped from 10.9% in 2018/1 to only 1.7% in 2019/1. All the differences between the treatment and control groups were statistically significant (P < 0.0001). The use of ICD/SL improved the academic performance of students.